Altitudinal wise assessment of soil physio-chemical properties of different agroforestry systems in Garhwal Himalaya, India - NG, Manitombi devi (Indian Journal of Agroforestry, 2025)
Agroforestry systems significantly influence soil properties, which are important indicators of soil health. The study was carried out to assess soil properties viz., moisture content, water-holding capacity, soil texture, bulk density, and chemical properties like pH, SOC, SCS and SOM in three prominent agroforestry systems, including agrihorticulture (Scattered fruit crops, agrisilviculture (tree on bunds) agrisilvihorticulture ( homegarden) of western Himalayas, Uttarakhand. Soil samples where collected from three elevations (800-1300m, 1300-1800m, and above 1800m) under agroforestry systems at two depths (0-15cm, 15-30cm). The results show that altitude significantly influences soil texture, with sand content increasing and clay content decreasing with elevation. Higher altitudes exhibited greater soil moisture and organic matter retention. The agrisilvihorticulture system, particularly at higher altitudes demonstrated superior water holding capacity, lower bulk density and higher SOC and SOM, making it most effective for improving soil quality. Converslely, the agrihorticulture system at lower elevation at higher bulk density and lower organic carbon content. Soil organic carbon stock declined with depth with the highest values observed in the top soil. This study emphsizes the potential benefits in enhancing soil fertility, moisture retention and carbon sequestration, emphasizing the importance of selecting appropriate systems for adapting to climate change and promoting sustainable land management in the himalayan region. The findings provide valuable insight for improving agroforestry practices in the region to promote soil health and agricultural productivity.